SELECTION AND ANALYSIS OF ENGINE OF FSAE 2010 - PEREIRA, ROBERT HARJONI (Universiti Teknologi Petronas, 2009)
The objective of this project is to study, select and analyze the engine. This report includes introduction, literature review, methodology, result and discussions, and conclusion. The scope of study includes the usage of computer aided engineering software for the modeling and analysis purposes of the project. Theoretical calculations will also be carried out to compare the results with reality. In the literature review there will be a simple and basic explanation on engine and controllers, the specifications for Honda CBR 600 F4i, Yamaha FZ6 S2 and Aprilia SXV engines, the analysis of turbocharging small engines. The methodology section will consists of the project methodology which gives an outline of the activities taking place and also the Gantt chart which gives the milestone period for each activity. The comparison and analysis of the engines will be discussed in the result and discussion section.